Er,Cr:YSGG 2780 nm Laser Treatment of Lip Melanin Hyperpigmentation - Manaf Taher Agha; Pavel Polenik; Mawada Hassan (Hindawi Limited, 2021)
Background. In the current research, Er,Cr:YSGG laser been used in ablative mode to peel the pigmentation, and many sessions were done to completely remove the melanin pigmentations. Materials and Methods. 85 patients were selected and Er,Cr : YSGG laser with 2780 nm wavelength in ablative mode (iPlus, Biolase, USA) was used to treat patients with dark lip melanin pigmentation, using gold handpiece and MZ 10 tip (diameter of 1 mm), and the parameters were set as follows: energy density 28.7 J/cm2, frequency 30 Hz, water cooling 100%, and air cooling 60%. Results. The vast majority of the patients (82.4%) had mild adverse effects after the lip depigmentation and 74.1% of patients reported complete improvement of the lip with a high satisfaction rate (84.7%) during the follow-up period with a low level of relapse. Conclusion. Er,Cr:YSGG 2670 nm is an effective tool to achieve excellent esthetic results in the treatment of lip melanin pigmentation; it is very well tolerated by patients with minimal adverse effects.